Dysregulated paired related homeobox 1 impacts on hepatocellular carcinoma phenotypes - Piorońska, Weronika; Nwosu, Zeribe C.; Han, Mei; Büttner, Michael; Ebert, Matthias; Dooley, Steven; Meyer, Christoph (BMC cancer, 2021)
Hepatocellular carcinoma (HCC) is a major cause of cancer-related death. Paired related homeobox 1 (PRRX1) is a transcription factor that regulates cell growth and differentiation, but its importance in HCC is unclear.